2006
DOI: 10.1074/jbc.m509612200
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Role for 1-Acylglycerol-3-phosphate-O-acyltransferase 2 in Adipocyte Differentiation

Abstract: Mutations in the 1-acylglycerol-3-phosphate-O-acyltransferase 2 (AGPAT2) gene have been identified in individuals affected with congenital generalized lipodystrophy (CGL). AGPAT2 catalyzes acylation of lysophosphatidic acid to phosphatidic acid, a precursor for both triacylglycerol (TAG) and phospholipid synthesis. Recent studies suggest that reduced AGPAT2 enzymatic activity may underlie the CGL clinical phenotype. To gain insight into how altered AGPAT2 activity causes lipodystrophy, we examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
86
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 36 publications
14
86
0
1
Order By: Relevance
“…Similar observations were reported in cultured OP9 cells, a cultured cell model for adipogenesis (8). Inhibiting Agpat2 expression in these cells using siRNA indicated that additional pathway(s) might exist to generate PA (8).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Similar observations were reported in cultured OP9 cells, a cultured cell model for adipogenesis (8). Inhibiting Agpat2 expression in these cells using siRNA indicated that additional pathway(s) might exist to generate PA (8).…”
supporting
confidence: 81%
“…Surprisingly, total glycerophospholipid levels in the livers of Agpat2 Ϫ/Ϫ mice were not very different from those of WT mice (7). Similar observations were reported in cultured OP9 cells, a cultured cell model for adipogenesis (8). Inhibiting Agpat2 expression in these cells using siRNA indicated that additional pathway(s) might exist to generate PA (8).…”
supporting
confidence: 73%
“…In vitro studies have shown that AGPAT2 is involved in the metabolism and differentiation of adipocytes; as such, knockdown of AGPAT2 expression reduces the synthesis and storage of triglycerides in preadipocytes and adipocytes, thus preventing the development of normal adipocyte morphology. 15 The abnormal appearance and reduced numbers of WAT adipocytes that we Figure 27. Pancreas, islet of Langerhans; aged wild-type (WT) Agpat2 þ/þ mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of TAG synthesis therefore provides a very plausible explanation for lipodystrophy in patients with genetic defects in the AGPAT2 gene. However, cellular studies have also demonstrated that disruption of AGPAT2 or BSCL2 inhibits not only lipid synthesis but also the normal induction of adipogenic gene expression during fat cell development (Gale et al 2006, Payne et al 2008. This may reflect the tight co-regulation of gene expression and lipid droplet formation in developing adipocytes or indicate that these proteins possess functions in addition to their proposed roles in lipogenesis.…”
Section: Tag Synthesismentioning
confidence: 99%